PUZZLE GAME THERAPY ON THE ABILITY OF NUMBERS IN CLASS VII OF MENTALLY DISABLED CHILDREN IN SLB JENETALASSA - Auria, Widya (EDUSTUDENT: Jurnal Ilmiah Pendidikan dan Pembelajaran, 2025)
Abstract. This study aims to determine the effect of puzzle play therapy on theability to recognize numbers in students with intellectual disabilities. The researchused a qualitative descriptive method with observation, interviews, anddocumentation as data collection techniques. The research was conducted in SLBJenetalassa and involved students with difficulty recognizing, naming, andsequencing numbers. The intervention was carried out through several stages:preparing the learning atmosphere, introducing printed numbers, guiding thestudents to trace and pronounce numbers, and engaging in puzzle games designedto match the numerical shapes. The analysis technique involved data reduction,data display, and drawing conclusions. The results showed an improvement in thestudents' ability to recognize numbers after the therapy. Students became morefocused, actively participated in learning, and were more responsive to number-related tasks. Puzzle play therapy stimulated cognitive development and waseffective in enhancing number recognition skills in students with special needs. Thismethod can serve as an alternative learning strategy for inclusive education settings,especially in developing mathematical foundations among children withintellectual disabilities.Abstrak. Penelitian ini bertujuan untuk mengetahui pengaruh terapi bermainpuzzle terhadap kemampuan mengenal angka pada anak tunagrahita.Penelitian ini menggunakan metode deskriptif kualitatif dengan teknikpengumpulan data berupa observasi, wawancara, dan dokumentasi. Lokasipenelitian dilakukan di SLB Jenetalassa dengan subjek siswa yang mengalamikesulitan dalam mengenal, menyebutkan, dan mengurutkan angka. Intervensidilakukan melalui beberapa tahapan, yaitu pengondisian suasana belajar,pengenalan angka cetak, latihan menebalkan dan menyebut angka, sertabermain puzzle angka yang sesuai. Teknik analisis data meliputi reduksi data,penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkanadanya peningkatan kemampuan siswa dalam mengenal angka setelahdiberikan terapi. Siswa menjadi lebih fokus, aktif mengikuti pembelajaran, danmerespons tugas-tugas angka dengan lebih baik. Terapi bermain puzzlemampu menstimulasi perkembangan kognitif dan efektif dalam meningkatkanketerampilan mengenal angka pada anak berkebutuhan khusus. Metode inidapat menjadi alternatif strategi pembelajaran yang menyenangkan, terutamadalam pengembangan dasar-dasar matematika bagi anak tunagrahita dilingkungan pendidikan inklusif.